Access to Holiday in Hematological Patients Managed in a Home Care Program: A Single-Center Experience. (April 2013) - Tendas, Andrea; Cupelli, Luca; Trawinska, Malgorzata Monika; Palombi, Massimiliano; Giovannini, Marco; Scaramucci, Laura; Brunetti, Gregorio; Cartoni, Claudio; Perrotti, Alessio; de Fabritiis, Paolo; Niscola, Pasquale
Home care–managed patients face several barriers making access to holiday difficult. During the trimester from June 15 to September 15, 2012, 54 hematological patients were attended by home care service; of these, only 6 (11%) have moved away from home to reach a holiday destination; advanced or terminal disease and high transfusion rate (>3 units/month) seems to negatively affect patients' access to holiday in our series. Larger studies should be designed to definitely clarify the main barriers to transfer, enabling physicians to plan interventions aimed to bypass these obstacles.